Recent evaluation about inflammatory mechanisms in nonalcoholic fatty liver disease - Song, Chong; Long, Xian; He, Jianbin; Huang, Yongpan (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is common chronic metabolic liver disorder which is associated with fat accumulation in the liver. It causes a wide range of pathological effects such as insulin resistance, obesity, hypertension, diabetes, nonalcoholic steatohepatitis (NASH) and cirrhosis, cardiovascular diseases. The molecular mechanisms that cause the initiation and progression of NAFLD remain fully unclear. Inflammation is regarded as a significant mechanism which could result in cell death and tissue injury. Accumulation of leukocytes and hepatic inflammation are important contributors in NAFLD. Excessive inflammatory response can deteriorate the tissue injury in NAFLD. Thus, inhibition of inflammation improves NAFLD by reducing intrahepatic fat content, increasing β-oxidation of fatty acids, inducing hepato-protective autophagy, overexpressing peroxisome proliferator-activated receptor- γ (PPAR-γ), as well as attenuating hepatocyte apoptosis and increasing insulin sensitivity. Therefore, understanding the molecules and signaling pathways suggests us valuable information about NAFLD progression.This review aimed to evaluate the inflammation in NAFLD and the molecular mechanism on NAFLD.